SISTEM INFORMASI CUSTOMER RELATION MANAGEMENT BERBASIS WEB PADA ISP (STUDI KASUS: PT. NUSANTARA TAMAMULTIMEDIA) - Purnomo, Heri (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2016)
PT. Nusantara Tamamultimedia (NT-Net) is a business that is engaged in the service called ISP (Internet Service Provider), to facilitate the preparation of reports and processes in serving customers, such as service how to attract customers, build and maintain good relationships the customer needed an information system, that is the information system customer relation management (CRM). This research aims to design the right CRM information systems at the ISP. In making the CRM information system, the method used is the System Development Life Cycle (SDLC) with several stages: 1. Analysis 2. Design 3. Implementation 4. Maintenance. The results of the study, namely the creation of a website Customer Relation Management Information System which is used to attract good customer service, build or maintain relationships with customers at PT. Nusantara Tamamultimedia.Â Keyword : CustomerÂ  Relation Management, Internet Service Provider , Information System, Website